Peran Kepala Sekolah Dalam Pengembangan Karakter pada Kurikulum Merdeka Di TKIT Az-Zahra Demak - Rosadi, Ima Dwi; Nela Veristika; Soedjono (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research aims to describe the role of the principal in developing student character at TKIT Az-Zahra Demak, especially in implementing the Independent Curriculum. The focus of this research is to understand the strategies, challenges and impact of school principal leadership on strengthening the character of early childhood. This research uses a qualitative approach with a case study method. Data was obtained through observation, in-depth interviews and documentation. The research results show that school principals have a strategic role in integrating character values ​​into learning activities and school culture. The school principal acts as a learning leader, facilitator and motivator for teachers and provides support in developing character-based programs. In addition, the implementation of the Independent Curriculum provides flexibility in designing contextual and meaningful learning for students. However, there are challenges in terms of developing teacher competency and collaboration with parents. This research concludes that the success of character development at TKIT Az-Zahra Demak is very dependent on the commitment of the school principal, collaboration between parties, and support from the school environment. The recommendations of this research include the need for continuous training for teachers and strengthening synergy between schools and families in supporting the implementation of the Independent Curriculum.